Ricoeurean Hermeneutics of Māra as the Theravāda Buddhist Symbol of Evil - Puttarakitvorakul, Pakpoom; Chokvasin, Theptawee; Saengkaew, Theerat (Journal of the Philosophy and Religion Society of Thailand, 2024)
In this research paper, we applied Ricoeurean hermeneutics in The Symbolism of Evil, a philosophical process that he employed to address the issue of evil through the phenomenology of confession, which considered the human fault, and the hermeneutics of symbols and myths of evil to explain the issue. Our analysis indicates that Māra remains in the mythological narrative in Buddhist studies, which caused the question of whether the Ricoeurean method will result in a more precise interpretation of Māra in certain respects. The results of the interpretation indicate that the evil that is already there is the one that leads to death. Humans are contaminated toward-death and transmit it to the world by residing in the world of the senses, which is confirmed through their fear. Nevertheless, human beings retain the authority to choose whether their course leads to life or death.